Instabilities, induced by a noise - Buts, V.A. (Вопросы атомной науки и техники, 2002)
The dynamics of systems, parameters of which are subject to casual forces are considered. The casual action can be as external, and to be generated by own random dynamics of a system. The most important features of such systems dynamics are chosen. First of all, their behavior is characterized by an alternation. In these systems (even linear) the properties, which are characteristic for a stochastic resonance, can be to exist. Instabilities, which are induced by a noise practically are not stabilized by nonlinearities.